Transformational nurse leadership attributes in German hospitals pursuing organization-wide change via Magnet® or Pathway® principles: results from a qualitative study - Joan Kleine; Julia Köppen; Carolin Gurisch; Claudia B. Maier (BMC, 2024)
Abstract Background Budget constraints, staff shortages and high workloads pose challenges for German hospitals. Magnet® and Pathway® are concepts for implementing organization-wide change and redesigning work environments. There is limited research on the key elements that characterize nurse leaders driving the implementation of Magnet®/Pathway® principles outside the U.S. We explored the key attributes of nurse leaders driving organization-wide change through Magnet®/Pathway® principles in German hospitals. Methods Using a qualitative study design, semi-structured interviews (n = 18) were conducted with nurse leaders, managers, and clinicians, in five German hospitals known as having started implementing Magnet® or Pathway® principles. The interviews were recorded and transcribed verbatim. Data were analyzed in Atlas.ti using content analysis. For the analysis, a category system was created using a deductive-inductive approach. Results Five leadership attributes and eleven sub-attributes were identified as main themes and sub-themes: Visionary leaders who possess and communicate a strong vision and serve as role models to inspire change. Strategic leaders who focus on strategic planning and securing top management support. Supportive leaders who empower, emphasizing employee motivation, individualized support, and team collaboration. Stamina highlights courage, assertiveness, and resilience in the face of challenges. Finally, agility which addresses a leader's presence, accessibility, and rapid responsiveness, fostering adaptability. Conclusions The study demonstrates leadership attributes explicitly focusing on instigating and driving organization-wide change through Magnet®/Pathway® principles in five German hospitals. The findings suggest a need for comprehensive preparation and ongoing development of nurse leaders aimed at establishing and sustaining a positive hospital work environment.